Актуальні правові проблеми підтримки розвитку стартапів в умовах російсько-української війни - Чуприна, А. (НДІ ПЗІР НАПрН України, 2023)
У статті досліджено проблематику діяльності стартапів, які перебуваються на стадіях розвитку Expansion (стадія розширення) та Exit (стадія «виходу») на поточному етапі російсько-української війни. Це завершальні стадії розвитку стартапів, після успішного проходження яких суб’єкт підприємницької діяльності перетворюється зі стартапу на інноваційне підприємство, оскільки перестає відповідати критерію незначного розміру та новоствореності. Саме тому ефективне проходження цих етапів розвитку дає змогу посилити економіку нашої держави ще одним великим підприємством, що одночасно позитивно впливає на ринок інноваційної продукції та здійснює нарахування до бюджету України шляхом сплати податків та зборів. В межах роботи було досліджено сучасний стан українського законодавства, актуальну правозастосовну практику та статистичні дані Національного банку України та останню судову практику національних судів різної юрисдикції. Автор дійшов до наступних висновків: аналіз статистичних досліджень дає змогу стверджувати, що низка ризиків, що були ключовими для стартапів у попередні роки, знизили свій вплив. Натомість у 2022-2023 роках найбільшими ризиками для стартапів є обставини пов’язані із проведенням бойових дій. Так, зокрема, ключове значення відіграє регіональне розташування виробництва стартапу. Разом з тим, ризик несприятливого географічного розташування стартапу може бути частково зменшений за рахунок державної підтримки стартапів певних галузей економіки. Значну підтримку стартапам було надано через програму релокації, яка, окрім своєї основної мети у вигляді збереження підприємств на прифронтовій території, вважається такою, що впливає на вину сторони зобов’язання та є підставою для зменшення розміру штрафних санкцій, а також відстрочення виконання судового рішення. Problem setting. The criminal attack of the Russian Federation on Ukraine without a declaration of war on February 24, 2022 fundamentally changed the entire system of legal relations of our state. Such armed aggression was also reflected in the entrepreneurial activity of startups as newly created subjects of entrepreneurial activity. Currently, the legal system of our country is in constant evolution in order to develop methods of supporting such subjects of entrepreneurial activity. Attention is also drawn to a number of law-enforcement aspects of startups that are not regulated at the level of regulatory and legal acts, which have a direct impact on the prospects of their development in Ukraine. Аnalysis of recent researches and publications. The issue of startup activity became the subject of scientific research by such scientists as S. V. Hlibko, O. V. Rozgon, I. V. Podrez-Ryapolova, A. S. Petkevich, A. V. Sherstobitov, I. V. Yashchyshina, and others. Within the framework of this scientific article, the specifics of the activity and support of startups in the conditions of martial law at the current stage of the Russian-Ukrainian war will be investigated. Тarget of the research is to examine the problems of startups that are in the Expansion and Exit stages of development at the current stage of the Russian-Ukrainian war. These are the final stages of the development of startups, which occurs after the stages of Pre-seed, Seed, Startup, Early Growth. After successfully passing the specified stages, the subject of entrepreneurial activity turns from a startup to an innovative enterprise, as it ceases to meet the criterion of small size and innovation. That is why the effective passage of these stages of development makes it possible to strengthen the economy of our state with another large enterprise, which at the same time has a positive effect on the market of innovative products and makes contributions to the budget of Ukraine through the payment of taxes and fees Аrticle’s main body. A startup is a high-risk type of entrepreneurship, as a result of which the challenges faced by representatives of Ukrainian business during the full-scale war mostly had a greater impact on startups. The analysis of the monitoring data allows us to state that the most observed influence is the regional location of business entities, while the negative influence of such factors as tax and regulatory pressure, the corruption component, lack of qualified employees, etc., was significantly reduced. Relocation is considered to affect the fault of the party to the obligation and is the basis for reducing the amount. Conclusions and prospects for the development. The analysis of statistical studies makes it possible to claim that a number of risks, which were key for startups in previous years, have reduced their impact. Instead, in 2022-2023, the biggest risks for startups are circumstances related to the conduct of hostilities. So, in particular, the regional location of the startup’s production plays a key role. At the same time, the risk of an unfavorable geographical location of a startup can be partially reduced due to state support for startups in certain sectors of the economy. Considerable support for startups was provided through the relocation program, which, in addition to its main goal of keeping enterprises in the front-line territory, is considered to affect the fault of the party to the obligation and is the basis for reducing the amount of fines, as well as delaying the execution of the court decision.
Keywords: стартап; релокація; виконання зобов’язань; виконання судового рішення; startup; relocation; fulfillment of obligations; fulfillment of a court decision